Numerical Simulation of Solar Air Heater using Paraffin Wax-Aluminum Compound as Phase Changing Material - Kumar, Atul; Bhandari, Prabhakar; Rawat, K.S. (Aptisi Transactions On Technopreneurship (ATT), 2021)
This paper presents a theoretical investigation of solar air heater using phase change material (PCM). PCM used in present configuration is homogenous mixture of paraffin wax with Aluminium powder. The purpose of using Aluminium powder with paraffin wax is to increase the thermal conductivity. PCM mixtures are encapsulated in cylinders and are used as solar absorbers. Using MATLAB program, the effect of different parameters is studied. It has been observed that with increase in mass flow rate, air outlet temperature decreases and freezing time of cylinder decreases. However, at constant mass flow rate, with increase in cylinder radius, air temperature decreases and while freezing time increase sharply. The different parameters have to be chosen such that performance of solar air heater can be optimized.